The tyranny of the meritocracy : democratizing higher education in America - Guinier, Lani (Beacon Press, 2015)
"Standing on the foundations of America's promise of equal opportunity, our universities purport to "serve as engines of social mobility" and "practitioners of democracy." But as acclaimed scholar and pioneering civil rights advocate Lani Guinier argues, the merit systems that dictate the admissions practices of these institutions are functioning to select and privilege elite individuals rather than create learning communities geared to advance democratic societies. Having studied and taught at schools such as Harvard University, Yale Law School, and the University of Pennsylvania Law School, Guinier has spent years examining the experiences of ethnic minorities at the nation's top institutions of higher education, and here she lays bare the practices that impede the stated missions of these schools. Guinier argues for reformation, not only of the very premises of admissions practices but of the shape of higher education itself, and she offers many examples of new collaborative initiatives that prepare students for engaged citizenship in our increasingly multicultural society"--